Fate of Chemical Activators in The Aqueous Environment: What Should We Do About It? - Muhammad A. A. Zaini; Tang S. Hui; Lee L. Zhi; Norulaina Alias (Graduate Program of Syiah Kuala University, 2016)
The commonly used activators in chemical activation of activated carbon are very toxic and poisonous to the aquatic environment. Finding trade-off solutions without compromising the quality of activated carbon and jeopardizing the environment have become the subject of considerable interest. This paper is aimed to shed some light on the inevitable release of chemical activators to the aqueous environment, and offers some possible solutions to overcome the emergence of secondary pollution.